The Evaluation of Effectiveness of Pedicle Subtraction Osteotomy on Thoracic Level in Spinal Deformity Patients - Emre Bal (Boğaziçi Tıp Dergisi, 2022)
INTRODUCTION: Classical instrumentation may be insufficient in the surgical treatment of rigid spinal deformities with structural changes in bone tissue. Many different types of osteotomy have been described to correct such rigid deformities. In this study, we aimed to evaluate the clinical and radiological results of pedicle subtraction osteotomy (PSO) applied at the thoracic level in patients with coronal and/or sagittal plane spinal deformity. METHODS: 61 of the 123 cases, who underwent PSO for spinal deformity between 2010 and 2013, were included in the study. Pre- and post-operative ortho-radiography was performed; angles (scoliosis, kyphosis, and lordosis angles) and global sagittal balance were measured. Duration of operation, bleeding and complications were noted. SF-36 scoring was used for clinical outcome. RESULTS: This study was consist of 30 male and 31 female patients including 28 scoliosis, 23 kyphosis and 10 ankylosing spondylitis cases. Post-operative mean Cobb angle was 62%, sagittal balance was 42%, kyphosis angle was 38%, thoracic kyphosis angle was 61%, and lordosis angle was 19.44% corrected (p<0.001). When radiological data were evaluated, significant improvement was observed in the angles of kyphosis and lordosis after PSO surgery. The eight parameters of SF-36 showed an increase in all patients, while the least change was observed in the pain parameter. DISCUSSION AND CONCLUSION: PSO surgical technique is effective in patients with spinal deformity with sagittal balance disturbance at the lumbar region as well as thoracic level.